Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus